2016
DOI: 10.1093/tropej/fmw056
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology: A New Focus of Kala-azar at High-Altitude Garhwal Region of North India: Table 1.

Abstract: Adult cases of visceral leishmaniasis (VL), predominantly males, have been reported in the past decade from natives of high altitude areas of North Indian state of Uttarakhand. We report 14 pediatric cases of VL, who were diagnosed and treated successfully over the past 7 years. All these children were born and brought up in this area and had never visited any of the endemic areas. High prevalence of pallor, splenohepatomegaly, thrombocytopenia and poor association with HIV are cardinal features of VL in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A decrease in the number or function of CD4 cells may cause recurrence, as in the case of patients receiving corticosteroids or chemotherapy, in transplant recipients, or in association with infection with HIV; in this scenario, a new therapeutic regimen may be required 49 51 .…”
Section: Visceral Leishmaniasis or Kala-azar (Black Fever)mentioning
confidence: 99%
“…A decrease in the number or function of CD4 cells may cause recurrence, as in the case of patients receiving corticosteroids or chemotherapy, in transplant recipients, or in association with infection with HIV; in this scenario, a new therapeutic regimen may be required 49 51 .…”
Section: Visceral Leishmaniasis or Kala-azar (Black Fever)mentioning
confidence: 99%
“…Sporadic VL cases have been reported from Kerala, Morena, and Malwa regions of Madhya Pradesh and Haryana [ 12 , 51 – 54 ]. Case reports of the disease from sub-Himalayan parts, including Uttarakhand, Himachal Pradesh, Jammu, and Kashmir, are of special interest because VL is typically a disease of low altitude [ 14 , 15 , 55 – 57 ]. In fact, leishmaniasis is reported as the most common cause of bone marrow infections in the North Himalayan region [ 58 ].…”
Section: Indian Subcontinentmentioning
confidence: 99%
“…Enlargement of the liver (hepatomegaly) is a common symptom in VL patients; 30-100% of VL patients with parasitological confirmation present with liver enlargement [2][3][4][5][6][7][8][9][10][11]. In addition, biochemical markers of hepatocellular damage, AST and ALT, are found to be elevated in the blood of these patients [2,[9][10][11][12]. Moreover, it has been reported that liver failure may be a direct cause of death in VL patients [13].…”
Section: Introductionmentioning
confidence: 99%